2012
DOI: 10.1016/s2221-1691(12)60251-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activity and bronchodialator effect of a polyherbal drug–Shrishadi

Abstract: The study reveals that the extracts possess antibacterial activity and antifungal activity in a dose dependent manner. This antimicrobial property may be due to presence of several saponins, further studies are highly needed for the drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“… Amaranthaceae Leaves Pneumonia and asthma Antihistaminic, anti-inflammatory, mast cell stabilizer and bronchoprotective effect. Inhibits action of histamine, acetylcholine and 5-HT [ 139 , 140 ] Albizia lebbeck Benth Moraceae Bark Flu, cough, lung problems Bronchodialator, Anti-allergic, Mast cell stabilizing property due to histamine release and cytokine expression of antigen –ige activated mast cells [ 141 , 142 ] Alstonia scholaris Fabaceae Bark, Leaves Asthma Bronchodialator, anti-tussive effect against sulfur dioxide induced mice coughing and citric acid induced guinea pigs coughing. Anti-asthmatic activity against histamine induced bronchoconstriction [ 143 , 144 ] Althaea officinalis L. Lythraceae Flowers, leaves, roots, fruits Asthma and bronchitis Cough suppressant activity in citric acid-induced cough reflex [ 145 ] Artemisia vulgaris Asclepiadaceae Leaves Asthma Bronchodilator due to anticholinergic and Ca 2+ antagonist mechanisms [ 146 ] Artemisia maritime Asteraceae Aerial parts Cough Bronchodilator activities mediated possibly through dual blockade of calcium channels and phosphodiesterase [ 102 ] Adhatoda vasica Capparidaceae Whole plant Cough, bronchitis, asthma Antiallergic, anti-anaphylact...…”
Section: Resultsmentioning
confidence: 99%
“… Amaranthaceae Leaves Pneumonia and asthma Antihistaminic, anti-inflammatory, mast cell stabilizer and bronchoprotective effect. Inhibits action of histamine, acetylcholine and 5-HT [ 139 , 140 ] Albizia lebbeck Benth Moraceae Bark Flu, cough, lung problems Bronchodialator, Anti-allergic, Mast cell stabilizing property due to histamine release and cytokine expression of antigen –ige activated mast cells [ 141 , 142 ] Alstonia scholaris Fabaceae Bark, Leaves Asthma Bronchodialator, anti-tussive effect against sulfur dioxide induced mice coughing and citric acid induced guinea pigs coughing. Anti-asthmatic activity against histamine induced bronchoconstriction [ 143 , 144 ] Althaea officinalis L. Lythraceae Flowers, leaves, roots, fruits Asthma and bronchitis Cough suppressant activity in citric acid-induced cough reflex [ 145 ] Artemisia vulgaris Asclepiadaceae Leaves Asthma Bronchodilator due to anticholinergic and Ca 2+ antagonist mechanisms [ 146 ] Artemisia maritime Asteraceae Aerial parts Cough Bronchodilator activities mediated possibly through dual blockade of calcium channels and phosphodiesterase [ 102 ] Adhatoda vasica Capparidaceae Whole plant Cough, bronchitis, asthma Antiallergic, anti-anaphylact...…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and clinical studies showed that it has potent bronchodilator,[10] anti-inflammatory,[11] and anti-anaphylactic[12] effects. It significantly improves the peak expiratory flow rate (PEFR) and forced vital capacity (FVC) in the patients of bronchial asthma.…”
Section: Resultsmentioning
confidence: 99%
“…In the extracts, total phenols and tannins were found in important concentrations, with greater abundance in the three extracts of ethyl acetate although also were found in lower concentration in the extracts of methanol and hexane. Tannins and phenols have been found in several Solanaceae species, such as S. xanthocarpum, S. nigrum Linn, and S. trilobatum, and its presence has been linked to the medicinal and therapeutic effects in diseases such as anti-ulcerogenic, anti-microbial, bronchodilator, anti-inflammatory, inductor of some human cancer cells apoptosis, and cycle cell arrest (21,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%